Impacts of ownership changes on emissions and industrial production: evidence from Europe - Chlond, Bettina; Germeshausen, Robert (Discussion paper, 2024)
Firm ownership is a major determinant for the economic performance of firms, and emissions of pollutants are often by-products of industrial production. We investigate the impact of ownership on pollutant emissions of firms and their industrial facilities in Europe jointly with their output, productivity, and other key economic outcomes. To disentangle the influence of ownership from other firm characteristics, we analyse the effects of ownership changes in an event-study approach. We find that facilities and firms do not change their emissions and emissions intensity if they remain in operation after a change in ownership. Firms that shut down after acquisition strongly reduce their emissions via reductions in output. The reductions cannot be attributed to the ownership change as they already start before acquisition. There is no evidence for transfers in pollution abatement technologies between target and acquiring parent company. Overall, we do not find environmental benefits from ownership changes.